A multicenter cross-sectional study on factors associated with caregiving appraisal in pediatric acute leukemia caregivers - Ouru, Phoebe Abonyo; Zheng, Hong; Lin, Zhi; Yang, Minghua (PloS one, 2025)
Caring for pediatric acute leukemia (PAL) patients poses significant psychological challenges for family caregivers, impacting their well-being and caregiving capacity. This multicenter study aimed to assess caregivers' perception of their caregiving role using the revised Caregiving Appraisal Scale (rCAS) and identify factors associated with negative and positive caregiving appraisals among caregivers of children with PAL. A cross-sectional survey was conducted across three hospitals affiliated with Central South University. The 4-domain rCAS assessed both positive (satisfaction, mastery) and negative (burden, environmental impact) caregiving appraisals. Patient clinical data as well as demographics of both patients and caregivers were used to perform univariate, correlation, and multivariate regression analyses, identifying predictors of caregiver psychological distress. Out of 111 recruited caregivers, 101 valid responses were analyzed. Univariate subgroup analysis showed that several caregiver- and patient-related factors were significantly associated with increased caregiver burden and environmental impact. For mastery and satisfaction, some factors were associated with higher appraisal scores while others were related to significantly lower scores. Correlation analysis showed that patient discomfort and difficulties significantly correlated with both negative and positive appraisals. The regression models revealed that the independent influencing factors contributed to about 23.9% of caregiver-perceived negative impact (P = 0.024) and 30.3% of caregiver-perceived positive impact (P < 0.001). Patient worry (P = 0.024), communication difficulties (P = 0.011), relationship to the patient (P = 0.017), and medical insurance type (P = 0.035) predicted negative appraisals while pain (P = 0.008), anxiety about surgical procedures (P = 0.022), relationship to the patient (P = 0.031), and caregiver educational level (P = 0.023) predicted positive appraisals. Caregivers of pediatric acute leukemia experience considerable psychological strain. Despite these challenges, some caregivers report significantly higher positive appraisals. Targeted interventions are needed to reduce caregiver burden and enhance positive caregiving outcomes.